Adsorption of phosphate on UiO-66-NH2 prepared by a green synthesis method. Issue 6 (December 2021) - Zhang, Xiaoting; Liu, Mingyu; Han, Runping
Abstract: In this study, a zirconium-based metal organic framework (UiO-66-NH2 ) was prepared with a green synthetic method for removal of phosphate from solution. Several characterization methods were performed and the adsorption property of UiO-66-NH2 toward phosphate was explored in batch mode. There was a good adsorption performance for phosphate with a wide range of pH (pH = 2–11) with a slight effect of salinity. The adsorption capacity was up to 43.9 mg·g –1 at 303 K from experiments. The adsorption isotherms can be better described by Langmuir, Temkin, and Koble-Corrigan model while adsorption kinetics can be well fitted by Pseudo-second-order, Double Constant and Elovich model. The process was spontaneous and exothermic and the major mechanism of phosphate adsorption was complexation. The spent adsorbent can be well regenerated using 0.01 mol·L –1 NaOH. The study shows that UiO-66-NH2 has the potential to remove phosphate from solution. Graphical Abstract: ga1 Highlights: The synthesis process of UiO-66-NH2 was relatively green and environmentally friendly. The UiO-66-NH2 exhibited significant adsorption capacity towards phosphate with a wide range of pH. There is high salt tolerance as well as good regeneration performance. The process of adsorption and desorption process toward phosphate was faster.